دور التكنولوجيا المالية في تحقيق الميزة التنافسية في المصارف السعودية -دراسة حالة مصرف الراجحي - بنعمر, اعطيات (جامعة الوادي - University of Eloued, 2023)
This study aims to identify the role of financial technology in creating competitive advantage for Al-Rajhi Bank and to explore the nature of their relationship. This research relies on an analytical-descriptive approach. Questionnaire is used as a tool for data collection and distribution to the employees of Al-Rajhi Bank in Riyadh City, with a sample of 280 employees. SPSS program is used to analyze the data. The study draws a number of results, the most important of which is that financial technology plays an important role in creating a competitive advantage in Al Rajhi Bank in its four dimensions (quality, delivery, cost, flexibility). This leads us to conclude that the strength of competitive advantage comes from financial technology. There is a positive relation between financial technology and competitive advantage. With the application of financial technology, banking services are improved and banks have a greater competitive advantage.
بنعمر، اعطيات. دور التكنولوجيا المالية في تحقيق الميزة التنافسية في المصارف السعودية -دراسة حالة مصرف الراجحي . مجلة رؤى اقتصادية . مج 13. العدد01. 2023/06/15 . جامعة الوادي [اكتب تاريخ الاطلاع] متاح على الرابط [انسخ رابط التحميل]
مقال
Keywords: التكنولوجيا المالية ؛ الميزة التنافسية ؛ الخدمات المصرفية ؛ مصرف الراجحي.; Financial Technology ; Competitive advantage ; Banking services ; Al-Rajhi Bank